A minimal description of morphological hierarchy in two-dimensional aggregates. Issue 34 (14th September 2015) - Das, Tamoghna; Lookman, T.; Bandi, M. M.
<x xml:space="preserve">Abstract</x> A single dimensionless parameter is proposed to characterise the morphology of two-dimensional aggregates by their structural randomness.